THE IMPORTANCES OF TELUK ANSON WHARF AS TRANSIT CENTRE OF MERCHANT VESSEL, 1882-1941 - Bipin A/L Babulal; Khairi Ariffin, (INTERNATIONAL JOURNAL OF HERITAGE, ART AND MULTIMEDIA (IJHAM), 2024)
This study is about the importance of the Teluk Anson wharf which used to be the transit centre of the merchant vessel in 1882 until 1941. It also was known as wharf in the British colonial administration since the opening in 1882. The development and construction of Teluk Anson port is very important as a wharf which handle the import and export transactions in the state of Perak, especially as the collection centre of tin ore and agricultural product for the districts of Lower Perak and other nearby places. The study is carried out by using the qualitative method which focusing the analysis on the primary sources such as Marine Annual Report, Federated Malays States Annual Report, Perak Annual Report, District Report and Perak Secretariat File which obtained from The National Archive of Malaysia. The study is focusing on the Teluk Anson wharf that located in the district of Lower Perak. The findings show that the port of Teluk Anson had significant role in trading activity, export and import of merchandise especially after commercial agricultural revolutions. The wharf of Teluk Anson became the focus of the merchant vessels from the Malay States, Southeast Asia, Europe and the United States. In conclusion, the infrastructural facilities which existed in the Teluk Anson wharf towns made this wharf as the main attraction in the Federated Malay States at the early of its opening until the World War-II. The implication of this study shows that the Teluk Anson wharf used to be the important wharf in the state of Perak during British colonial era.